Cyclodextrins in pharmaceutical nanoparticles - Dominique Duchêne; Gilles Ponchel; Denis Wouessidjewe; Amélie Bochot (ՀՀ ԳԱԱ հրատ.)
Cyclodextrins have been used in the development of pharmaceutical nanoparticles.
Keywords: Biology; Pharmacology